ANALYSIS OF DIFFERENT TREATMENTS OF MATERIALS INTENDED FOR MATTRESS COVERS - BOHM Gabriella; ŞUTEU Marius Darius; DOBLE Liliana; FETEA Lucian (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork)
The study on the chemical treatment of mattress cover materials for domestic and medical use is particularly important to understand how these materials can be improved in terms of resistance to different factors and durability in different contexts. In this paper, the materials for making three mattress covers (two mattress covers for home use and one mattress cover for hospital/medical care) were treated and tested in order to obtain basic information about the chemical treatment of fibers in mattress covers. Chemical treatments applied to materials can significantly influence their quality, strength and durability. It is essential to achieve the desired performance depending on the use of the mattress cover. The tests performed have provided valuable basic information regarding the behaviour of treated materials under different conditions, giving a clearer picture of their strength and the potential benefits or disadvantages of the chemical treatments applied. We noticed that chemically treated materials showed greater stain resistance and are easier to clean compared to untreated ones. Also, chemical treatments have helped to increase the durability of materials, thus extending the life of mattress covers. We used materials such as cotton, polyester and microfiber to make the mattress covers, and then subjected them to various chemical treatments to test their resistance to various external factors, such as blood stains or other liquids.